2020
DOI: 10.18502/sjms.v15i4.8166
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Knowledge of Cervical Cancer Screening among Female Nursing Students: An Interventional Educational Program

Abstract: Background: Cervical cancer is a growing health risk facing women worldwide with the human papillomavirus (HPV) as the primary underlying cause. Pap smear is a simple screening test that can detect early changes in cervical cells, which might develop into cancer cells. Raising awareness of cervical cancer prevention has a significant impact on decreasing the burden of the disease. The aim of the study is to assess female nursing students' knowledge on early detection and screening of cervical cancer, and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the current study, the knowledge scores of the intervention group was higher than control group and pretest intervention group, and significant statistical different between the groups, By using the interference program that promoted awareness and health education about cervical cancer and it's prevention and screen, this is similar to a study were conducted in Indonesia, where the results showed that the post-test score mean in the experimental group was 97.20 and the control group 56.50 with the p value 0.000 (p< 0.05) [10] , also similar to study done in Saudi Arabi [9] similar to study were conducted in Ghana (22) . However, the current study women should be directed to educate and promote awareness of women to the risk factors of cervical cancer and to the need for screening programs and the administration of the vaccine [24] , also similar to study done in village in Gurugram [18] , and similar to result of study done in India [23] .…”
Section: Effect Of Educational Program On Intervention Groupsupporting
confidence: 81%
See 2 more Smart Citations
“…In the current study, the knowledge scores of the intervention group was higher than control group and pretest intervention group, and significant statistical different between the groups, By using the interference program that promoted awareness and health education about cervical cancer and it's prevention and screen, this is similar to a study were conducted in Indonesia, where the results showed that the post-test score mean in the experimental group was 97.20 and the control group 56.50 with the p value 0.000 (p< 0.05) [10] , also similar to study done in Saudi Arabi [9] similar to study were conducted in Ghana (22) . However, the current study women should be directed to educate and promote awareness of women to the risk factors of cervical cancer and to the need for screening programs and the administration of the vaccine [24] , also similar to study done in village in Gurugram [18] , and similar to result of study done in India [23] .…”
Section: Effect Of Educational Program On Intervention Groupsupporting
confidence: 81%
“…The current study showed higher percentages of correct responses regarding the presence of cervical cancer, the possibility of its early diagnosis, it's signs and symptoms, the presence of vaccine for protection against this virus (HPV), cervical screening important because it detects early signs of cervical cancer or any abnormal change in cervix, these results better from a study done in Aira Hospital, Ethiopia, where About 400 (95.0%) of the study participants ever heard of cervical cancer [14] , and similar to result done in South-Eastern Nigeria where the majority of the respondents have heard of cervical cancer screening (68.8%) [15,16] . Lowest percentages of correct responses regarding the risk factor of cervical cancer such as giving birth to more than five children, involvement of sexual act an early age, presence of multiple partners and early menarche and late menopause, similar low percentages of correct answers was found regarding the vaccine such as its type, type of vaccine, Number of shots required and the necessity of having booster dose after five years, this is because no program is available at the PHCCs about cervical cancer and its risk factor and in addition to vaccine against HPV not available in Iraq, since primary level of health care is the best site for health education about different diseases comparing with study done in Saudi Arabia [9] .…”
Section: Knowledge Of Iraqi Women Regarding Cervical Cancer Screening...mentioning
confidence: 73%
See 1 more Smart Citation
“…As suggested by the key informants in the qualitative study more efforts are needed to promote capacity building for health professionals. An education intervention study from Saudi Arabia for nursing students suggested improved knowledge among nursing students regarding cervical cancer screening after the education intervention [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPV ile ilgili eğitim kampanyalarının serviks kanseri taramasını artırdığına dair kanıtlar, bu kampanyaların mülteci grupta da etkili olabileceğini düşündürmektedir. [11][12][13][14][15] Kadınlarda serviks kanseri görülme sıklığının yüksek ancak tarama oranlarının özellikle de mültecilerde düşük olduğu göz önüne alındığında, geliştirilmiş HPV farkındalığı serviks kanseri eşitsizliklerinin azaltılmasında önemli bir rol oynayabilir. Ülkemizde mülteci kadınlara bu konuda yapılan çevrim içi çalışmaya rastlanmamış olup, HPV farkındalığı kapsamında mülteci kadınlara özgü, ulaşılabilir ve aktif katılım sağlayabilecekleri bir eğitim uygulanması hedeflenmiştir.…”
unclassified